2014
DOI: 10.5194/hessd-11-4131-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mobilisation or dilution? Nitrate response of karst springs to high rainfall events

Abstract: Abstract. Nitrate (NO3-) contamination of groundwater associated with agronomic activity is of major concern in many countries. Where agriculture, thin free draining soils and karst aquifers coincide, groundwater is highly vulnerable to nitrate contamination. As residence times and denitrification potential in such systems are typically low, nitrate can discharge to surface waters unabated. However, such systems also react quickest to agricultural management changes that aim to improve water quality. In respon… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 51 publications
(59 reference statements)
0
20
0
Order By: Relevance
“…To find out the correlation between rainfall and [DN], we train three fitting models according formula . First‐order exponential decay best describes the correlation between [DN] and rainfall (mm) (Figure ), which is likely to be associated with the dilution affect (Huebsch et al., ). The equations best describing surface and subsurface runoffs at CQ are as follows: normalC1=9.49×expfalse(normalPfalse/33.53false)+0.32false(normalr2=0.89false) normalC2=20.47×expfalse(normalPfalse/11.76false)+0.50false(r2=0.95false)where Equation and belong to surface runoff and subsurface runoff, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To find out the correlation between rainfall and [DN], we train three fitting models according formula . First‐order exponential decay best describes the correlation between [DN] and rainfall (mm) (Figure ), which is likely to be associated with the dilution affect (Huebsch et al., ). The equations best describing surface and subsurface runoffs at CQ are as follows: normalC1=9.49×expfalse(normalPfalse/33.53false)+0.32false(normalr2=0.89false) normalC2=20.47×expfalse(normalPfalse/11.76false)+0.50false(r2=0.95false)where Equation and belong to surface runoff and subsurface runoff, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To find out the correlation between rainfall and [DN], we train three fitting models according formula (5). First-order exponential decay best describes the correlation between [DN] and rainfall (mm) (Figure 8), which is likely to be associated with the dilution affect (Huebsch et al, 2014). The equations best describing surface and subsurface runoffs at CQ are as follows:…”
Section: Correlation Between Rainfall and [Dn]mentioning
confidence: 99%
“…With respect to the common dual‐flow concept for groundwater flow in karst aquifers (Atkinson, ; Ford & Williams, , ; Goldscheider & Drew, ; Kiraly, ; White, ), the observed pattern at the Wiesent source reflects the diffusive flow component through fractures and pores. In contrast to the faster reacting conduit flow system that transports water along pipe‐like conduits and cave stream channel, the diffusive flow reflects NO3 average values and long‐term trends (Huebsch et al, ). Subsequently, NO3 likely has accumulated over decades in the deep karst aquifer and seasonal variations became negligible.…”
Section: Discussionmentioning
confidence: 99%
“…The Cl − excess could in part be balanced by excess Ca 2+ and Mg 2+ that does not account for carbonate weathering. When assuming that this cation excess stems from fertilizer use in the upstream part of the catchment, it supports the hypothesis that fertilizers are more pronounced in upstream river sections and may have entered the river via diffusive flow in the present karst system (Huebsch et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Fertilizer and pesticide pollutants such as nitrate and atrazine are commonly detected in shallow carbonate aquifers of southeastern Minnesota due to agricultural practices on the surface. These chemicals migrate down through the vadose zone, and may accumulate in the epikarst and/or saturated zone (Kamas et al, 2015;Huebsch et al, 2014). For example, Alexander et al (1999) reported that an anthropogenic Ca+Mg / Cl+NO 3 chemical component of up to 6 meq/kg is detectable in some at Garden of the Gods indicates that this area of the cave is a significant focal point for discharge of vadose zone waters held in storage above the cave.…”
Section: Study Areamentioning
confidence: 99%